2017
DOI: 10.1038/ncomms15999
|View full text |Cite
|
Sign up to set email alerts
|

Generation and comparison of CRISPR-Cas9 and Cre-mediated genetically engineered mouse models of sarcoma

Abstract: Genetically engineered mouse models that employ site-specific recombinase technology are important tools for cancer research but can be costly and time-consuming. The CRISPR-Cas9 system has been adapted to generate autochthonous tumours in mice, but how these tumours compare to tumours generated by conventional recombinase technology remains to be fully explored. Here we use CRISPR-Cas9 to generate multiple subtypes of primary sarcomas efficiently in wild type and genetically engineered mice. These data demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 58 publications
(89 reference statements)
0
81
0
Order By: Relevance
“…10). The mutational frequency in the Kras-induced sarcomas was very similar to sarcomas that arise in Trp53 fl/fl ; Kras LSL-G12D mice treated with IM adeno-Cre (11).…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…10). The mutational frequency in the Kras-induced sarcomas was very similar to sarcomas that arise in Trp53 fl/fl ; Kras LSL-G12D mice treated with IM adeno-Cre (11).…”
Section: Resultsmentioning
confidence: 62%
“…Assessment of Kras recombination. Kras recombination in sarcoma cell lines was assessed using a PCRbased assay as previously described (11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we also observed several differences in tumor phenotype between p107-mutated and p130mutated tumors, indicating potential biological differences between SCLC tumors with these genotypes. CRISPR-mediated knockout of genes has been particularly useful for modeling loss-of-function mutations in tumor suppressor genes, such as those as demonstrated here, as well as in other models (25,27,30,32). Other studies have demonstrated the ability to generate gain-of-function alterations, such as chromosomal rearrangements (26), as well as homologous recombinationmediated activation of oncogenes (25), albeit at a very low efficiency in the latter case.…”
Section: Discussionmentioning
confidence: 80%
“…The development of the CRISPR-Cas9 system for genome editing in mammalian cells (22)(23)(24) has revolutionized the field of cancer research, enabling rapid validation of candidate oncogenes and tumor suppressor genes both in vitro as well as in vivo. This has been especially useful when combined with GEMMs of various cancers (25)(26)(27)(28)(29)(30)(31)(32). By bypassing the need to generate new germline or conditional alleles for each gene of interest, the CRISPR-Cas9 Significance SCLC is a deadly disease for which treatment outcomes have not improved significantly for over 30 y due to the lack of effective new therapies.…”
mentioning
confidence: 99%